Handelsbetrekkinge tussen Suid-Afrika en Nederland in historiese perspektief, 1910-1990: Vryhandel en neutraliteit in die twintigste eeu (Historia, 2021)
Daar was groot verwagtinge dat Nederland en Suid-Afrika sterk handelsverbintenisse in die twintigste eeu sou ontwikkel. Die verwagtinge was gebaseer op vroeë Nederlandse immigrasie na die Transvaal en die vestiging van die Nederlandse Bank in Suid-Afrika. Hierdie artikel wys egter op die uiteenlopende struktuur van die twee lande se ekonomieë en die skaal waarop handel tussen die twee lande gedurende die twintigste eeu ontplooi het. In die periode tot 1960 was Nederland 'n beperkte handelsvennoot van Suid-Afrika, met minder as 3% van totale invoer uit Nederland en minder as 3% van totale uitvoer van SA na Nederland. Ná 1960 het hierdie posisie wesenlik onveranderd gebly, hoewel volumes toegeneem het.It was thought that extensive trade relations would develop between South Africa and the Netherlands in the twentieth century. These expectations were based on early Netherlands immigration to the Transvaal and the establish-ment of the Netherlands Bank in South Africa. This article notes the diver-gent structure of the two economies and the scale of trade between the coun-tries during the twentieth century. It deals with the historic expectations of extensive trade. Attention is then given to de facto trade. In the period up to 1960 the Netherlands was only a limited trading partner of South Africa, with less than 3% of total imports from the Netherlands and less than 3% of total exports to that country. After 1960 this relationship remained virtually unchanged, although volumes increased. This can be attributed to the differ-ence in factor endowment between the two countries and the international phenomenon of increasing international trade between countries of similar economic structure rather than between primary producer and first world countries.
Keywords: History; South Africa; Trade agreements; The Netherlands; Wassenaar; Trade; Bilateral Conference Historians of the Netherlands and South Africa 2000